PREPARASI PEMBUATAN COCOFOAM DARI SERABUT KELAPA - I D. K. Anom, ; Bambang Setiaji, ; Wega Trisunaryanti, ; Triyono, (Matematika dan Sains, 2010)
A preliminary study had been conducted on the making of cocofoam from coco fiber using diluted latex-water mixture. Coco fiber was cleaned and washed, and then dried up in the sun. Then, coco fiber was mixed with diluted latex-water mixture in several weight variations (w/w) 5:3, 5:4, 5:5, 5:6, 5:7 and 5:8. The mixture of coco fiber with the diluted latex-water was molded, and the result was called cocofoam. Cocofoam was vulcanized by using steam with duration variation 30, 60 and 90 minutes. After vulcanization cocofoam was dried up in room temperature for 36 hours. Then, the elasticity test was carried out by giving loads on its surface with weight variation 5, 10, 15, 20, 25, 30, 35, 40, 45 and 50 kg. The result showed that the best quality cocofoam was produced from coco fiber blended with diluted latex-water mixture 5:6. In direct observation, this result didnt show latex clod on cocofoam product, and the elasticity value was quite good. The C-56 cocofoam vulcanization steamed for 90 minutes showed increasing thickness about 22%, elasticity test showed the decreasing thickness for 2,04% in average, and the C-56 cocofoam density is 0,7905 g/cm3.3.